Voltage instability analysis on the Sabah grid system: a case study my - Songkin, Myjessie (2013)
With the development of the power system, voltage stability has become a major concern in planning and operating electric power system. The blackout problem has been associated with not only transient stability but also voltage stability. Voltage Instability in the Sabah Grid System has resulted in several major system failures. The recent major system failure due to the voltage instability happened on the 30